Low‐Level Alcohol Consumption in Children 11–12 Years Old Is Linked to Neural Substrates Involved in Reward Processing and Inhibitory Control: Results From a Brain‐Wide Association Study. - Jackson, Isabella F.; Meyer, Francisco A. C.; Sullivan, Ryan M.; Watts, Ashley L. (Alcohol, Clinical & Experimental Research, 2026)
Background: We comprehensively examined the cross‐sectional and prospective structural (i.e., cortical volume and subcortical volume) and functional (i.e., activation during the Monetary Incentive Delay task and the emotional N‐back task) neural correlates of alcohol sipping in early adolescence across two waves of data from the Adolescent Brain Cognitive Development (ABCD) Study (baseline: ages 9–10, n = 7555; 2‐year follow‐up: ages 11–12, n = 5892). Methods: Generalized linear mixed models examined individual brain regions of interests' ability to predict alcohol sipping. Results: At the 2‐year follow‐up, sipping was associated with activation during the MID large reward versus neutral contrast in 12 regions (e.g., nucleus accumbens), and activation during the MID large loss versus neutral contrast in 13 regions (e.g., insula). Conclusions: These findings aligned with existing literature on alcohol consumption, with neural regions involved in reward and inhibitory control being associated with alcohol sipping. Given that the findings from year 2 mirror several well‐established neural correlates of alcohol use and alcohol use disorder in adults, alcohol sipping may be an important phenotype for predicting future alcohol involvement.